Oliy ta’lim tizimida kredit modul tizimidan foydalanishning metodik asoslari - Ismoilova Iroda Erkinovna (SAMARALI TA’LIM VA BARQAROR INNOVATSIYALAR JURNALI, 2024)
This article describes the credit module system and its advantages in the educational system. The credit module system describes the steps of evaluation, independent education, and organization of educational processes.